Kebijakan Pemerintah Provinsi Jawa Timur dalam Penanganan Tindak Kekerasan pada Perempuan dan Anak - Jumanah, Jumanah; Nugroho, Arif; Rizki, Ari; Nurhanifah, Jihan; Agusvina, Alfiah; Pratiwi, Tiara Indah; Nurmaya, Siti (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2024)
(East Java Provincial Government Policy in Handling Violence against Women and Children) This research aims to dig up information and analyze in more depth related to policies towards women and children with the realization of protection for victims of violence as a form of policy of the East Java Provincial Government. Forms of protection for victims are needed to fulfill victims' rights. Domestic Violence (KDRT) is a serious problem in the marriage sector in Indonesia, and domestic violence continues to increase from year to year. Most victims of domestic violence are women and children. To prevent and save victims of domestic violence, protection must be provided to them. The following research is a literature study using a qualitative approach. Based on survey results, domestic violence against women and children is caused by strong discrimination against women due to the strong patriarchal culture. Apart from that, education and poverty factors also play a role. Law enforcement against perpetrators of domestic violence is also weak. Protection for victims of domestic violence includes preventive efforts such as 24-hour temporary protection by the police and courts as well as placing victims in safe locations. Apart from that, there are curative measures carried out at certain stages. Also in the form of repressive protection, namely arresting and imprisoning the perpetrator so that the victim feels safe. An obstacle to protection from domestic violence is the tendency of victims to withdraw their complaints for emotional reasons or because they are worried about the burden on their lives in the future. Apart from that, it is difficult to collect evidence to detect incidents of violence in the household. ABSTRAK Penelitian ini bertujuan untuk menggali informasi dan menganalisis secara lebih mendalam terkait kebijakan terhadap perempuan dan anak dengan perwujudan perlindungan terhadap korban kekerasan sebagai bentuk kebijakan Pemerintah Provinsi Jawa Timur. Bentuk perlindungan terhadap korban sangat dibutuhkan untuk memenuhi hak-hak korban. Kekerasan Dalam Rumah Tangga (KDRT) merupakan masalah serius dalam bidang perkawinan di Indonesia, dan KDRT terus meningkat dari tahun ke tahun. Sebagian besar korban KDRT adalah perempuan dan anak-anak. Untuk mencegah dan menyelamatkan korban KDRT, perlindungan harus diberikan kepada mereka. Penelitian berikut ini merupakan studi literatur dengan menggunakan pendekatan kualitatif. Berdasarkan hasil survei, KDRT terhadap perempuan dan anak disebabkan oleh masih kuatnya diskriminasi terhadap perempuan akibat masih kuatnya budaya patriarki. Selain itu, faktor pendidikan dan kemiskinan juga turut berperan. Penegakan hukum terhadap pelaku KDRT juga masih lemah. Perlindungan terhadap korban KDRT meliputi upaya preventif seperti perlindungan sementara selama 24 jam oleh kepolisian dan pengadilan serta menempatkan korban di lokasi yang aman. Selain itu, ada upaya kuratif yang dilakukan pada tahap-tahap tertentu. Juga dalam bentuk perlindungan represif, yaitu menangkap dan memenjarakan pelaku agar korban merasa aman. Kendala perlindungan dari KDRT adalah kecenderungan korban menarik kembali pengaduannya karena alasan emosional atau karena khawatir akan membebani kehidupannya di masa depan. Selain itu, sulitnya mengumpulkan bukti-bukti untuk mendeteksi kejadian kekerasan dalam rumah tangga.